The Mediating Roles Of Ethical Practices In The Relationship Quality And Cost Performance Of Multifarious Infrastructure Projects In Northern Region Of Nigeria - Shuaib, Muhammad Rabiu (2022)
The construction industry has been associated with deteriorated and adversarial working relationship among supply chain partners. This has been reported to affect the industry performance in terms of cost. In other word, projects attained significant cost performance through working relationships of the supply chain (SC) partners in construction. This study aimed at developing a model for the mediation role of ethical practice on a relationship between relationships quality (RQ) and cost performance of Multifarious Infrastructure Projects (MIPs) in Nigeria. Four main attributes of RQ were identified from extent literature as trust, commitment, teamwork and performance satisfaction (PS). The study introduced ethical practice as a mediating construct with two-dimensional measure as pre-contract ethical practice (PreCEP) and post-contract ethical practice (PoCEP) to mediate the relationship between RQ as the independent variable (IV) and cost performance (CP) as the dependent variable (DV). Using purposive non-probability sampling technique, 289 valid quantitative sample data were collected. The study focused on key informants such as directors and managers within several organizations involved on multifarious infrastructure projects (MIPs) in Nigeria.